Pengaruh Kualitas Produk, Persepsi Harga dan Ulasan Produk Terhadap Keputusan Pembelian Online Hijab Pashmina Kaos (Studi Mahasiswi UIN Suska Riau) - Fauziyyah Zahira; Ainun Mardiah; Rhonny Riansyah (Al-Manar Journal of Public Administration and Management, 2025)
The purpose of this study was to determine whether the influence of Product Quality, Price Perception and Product Reviews on Online Purchase Decisions for Hijab Pashmina shirt on UIN Suska Riau Students. The data collection technique used a questionnaire. The type used in this study is a quantitative type about the influence between variables. The research data was analyzed using SPSS version 25. The population in this study were 100 UIN Suska Riau students using the purposive sampling method. Data analysis used in this study was quantitative with multiple linear regression methods. Based on the results of the simultaneous test, it can be seen that the variables of Product Quality, Price Perception and Product Reviews together influence the Online Purchase Decision for Hijab Pashmina shirt on UIN Suska Riau Students. Then a partial test, from this test it can be seen that the Product Quality variable has a significant effect on the Purchase Decision and the Price Perception variable has a significant effect on the Purchase Decision and Product Reviews have a significant effect on the Purchase Decision. The R square value obtained was 0,615 or equal.